Asymptotic behavior of solution of the inverse problem for weakly nonlinear ultraparabolic equation - Protsakh, N.P. (Carpathian Mathematical Publications, 2013)
The inverse problem with the integral overdetermination condition for a weakly nonlinear ultraparabolic equation with unknown time-dependent multiplier of the right-hand side of the equation is considered. The conditions when a weak solution decreases to zero as the time variable increases are found.